Indicators of landscape organization and functionality in semi-arid former agricultural lands under a passive restoration management over two periods of abandonment - Tabeni, Maria Solana (2016)
Abandoned lands previously used for agricultural purposes may constitute an opportunity for understandingthe variables involved in the restoration of native ecosystems over time. In this study, weassessed the functional status of an abandoned farmland currently used for conservation, using a methodologybased on indicators of landscape organization and soil surface. We analyzed changes in plant cover,patch and interpatches structure and several soil surface properties during two periods of land abandonment(less and more than 40 years). Using this methodology, we characterize the potential of theecosystem to capture and transfer resources, and the state of functional properties such as infiltrationcapacity, soil stability and nutrient cycling.We detected a significant development of the shrub layer and an increase of the number, type andarea occupied by vegetated patches in old fields. The contribution of vegetated patches to the recovery ofstability, infiltration and nutrient functions was significant at the local scale. Nonetheless, when analyzingthe landscape as a whole only the nutrient cycling index was significantly higher in old fields. The lackof improvement of the stability and infiltration in old fields can lead to further degradation and indicatesthat even though vegetation cover may have improved over time in old fields, the current cover mightnot be enough to prevent further degradation by erosion. Our results reinforce the importance of usingfunctionality indexes in future studies focused on adequate restoration measures to protect the functionof desert ecosystems, especially when aimed for biodiversity conservation. Hence, the use of monitoringsystems based on organization and function indicators is a useful tool to represent the current state andpotential recovery of previously disturbed ecosystems, provided that the time scale is taken into account.